Predator and prey: the role of the round goby Neogobius melanostomus in the western Baltic. Issue 2 (7th February 2017) - Oesterwind, Daniel; Bock, Christiane; Förster, Anja; Gabel, Michael; Henseler, Christina; Kotterba, Paul; Menge, Marion; Myts, Dennis; Winkler, Helmut M.
ABSTRACT: Different studies on the position of the non-indigenous species Neogobius melanostomus within the coastal food web of the Pomeranian Bay (western Baltic) were performed, resulting in a quantitative and qualitative species list of prey organisms found in the stomachs of the invader and an estimation concerning the importance of round goby as prey for different resident predators. It seems that the colonization process is not fully completed yet, but the results reveal that the species is already established in the food web 16 years after the first observation within the study area. The results show that N. melanostomus feed upon a wide range of different resident organisms. While a direct predation effect on native fish species appears rather unlikely, indirect effects such as competition cannot yet be excluded. In addition, our results reveal an ontogenetic diet shift and that the round goby itself already serves as an important prey for piscivorous fish and seabirds. Finally, we formulate different hypotheses based on our results which will require further research.